Are the future nurses geared to protect themselves from blood borne viruses? A descriptive cross-sectional study from Sri Lanka - Piyumanthi, Ranasingha A. P.; Isuruni, Napagoda A. Y.; Abeyrathne, Geekiyanage N. U.; Rupasinghe, Sanduni R.; De Silva, Lahiru N.; Kottahachchie, Jananie; Goonewardena, Sampatha E. (International Journal Of Community Medicine And Public Health, 2020)
Background: Nurses have a high risk of being exposed to blood borne viruses (BBV) during their day to day practices and knowledge on transmission is important. The objective was to describe the knowledge in a selected Nursing Training School in Western Province, Sri Lanka and their associated factors of transmission of BBV, among nursing students in a selected Nursing Training School in Western Province and their associated factors in Sri Lanka. Methods: A descriptive cross-sectional study was carried out among 209 nursing students from a nursing school in Sri Lanka. Data collection was done using a self-administered questionnaire. Data was analysed using SPSS software version 15.0. Statistical significance was tested at p<0.05. Results: Majority (57%) had poor knowledge on transmission of BBV. Most gave correct answers for transmission of HIV and Hepatitis B virus 91%, 64% (HBV) by needle stick injury (82%, 87%), through blood transfusion (90%, 80%), mother to child at birth (90%, 64%), through organ and for transmission of HBV via tattooing/piercing, 58% gave correct answers transplant (80%, 66%), direct contact with blood (75%, 62%), through unprotected sexual intercourse (93%, 50%) and tattooing/ piercing (48%, 58%). Many had poor knowledge on transmission of HIV and HBV via sharing household equipment (50%, 84%), by kissing/hugging (57%, 75%), through mosquito bites (76%, 86%), by swimming in pools (80%, 87%), by eating contaminated food (81%, 88%) and through exposure to saliva/tears/stools and urine (89%, 92%). There was a statistically significant association between knowledge on transmission of BBV with higher academic year and older age (p<0.05). Conclusions: BBV transmission needs further emphasis on the curriculum for future nurses to deliver to their utmost capabilities in the future.